The IMPROVING STUDENTS’ READING COMPREHENSION BY USING QUESTIONING TECHNIQUES IN NARRATIVE TEXT - Yessica Elisabeth Sinabariba (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
This study attempts to improve students’ reading comprehension by using questioning technique. This study was conducted by applying classroom action research. The subject of the research was class X-4 SMA N.1 Sei Rampah which consisted of 30 students. The research was conducted in two cycles, cycle I of three meeting and cycle II consisted of three meetings. The instruments for collecting data were quantitative data namely reading comprehension test and qualitative data namely, diary notes, observation sheet and questionnaire. Based on reading comprehension test scores, students score kept improving in every test of reading. Based on diary notes, observation sheet and questionnaire sheet it was found that the students were active and enthusiastic in learning reading through questioning techniques. The result of the research showed that questioning techniques significantly improved students’ achievement in reading comprehension.